1989
DOI: 10.1557/proc-174-109
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Property-Microstructural Relationships in Abalone Shell

Abstract: The microstructure and mechanical properties of abalone shell were studied. It was found that fracture strength, αf, is 180 MPa, and fracture toughness, KIC, is 7 ± 3 MPa-m1/2; these values are comparable with or better than most “high technology” ceramic materials. The microarchitecture of the nacre section of the red abalone shell is similar to a “brick and mortar” structure, where CaCO3is the brick and organic matter is the mortar, constituting 95% and 5% of the microstructure by volume, respectively. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
102
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(107 citation statements)
references
References 10 publications
4
102
1
Order By: Relevance
“…In contrast, monolithic CaCO 3 showed a work of fracture that was about 3000 times less than that of the composite nacre material. It should be noted that this work of fracture is not identical to the toughness measured by Sarikaya et al [134]. The work-of-fracture is the area under the stress-strain curve and is deeply affected by gradual, graceful fracture, whereas the fracture toughness does not incorporate this entire process.…”
Section: Nacreous Shellscontrasting
confidence: 58%
“…In contrast, monolithic CaCO 3 showed a work of fracture that was about 3000 times less than that of the composite nacre material. It should be noted that this work of fracture is not identical to the toughness measured by Sarikaya et al [134]. The work-of-fracture is the area under the stress-strain curve and is deeply affected by gradual, graceful fracture, whereas the fracture toughness does not incorporate this entire process.…”
Section: Nacreous Shellscontrasting
confidence: 58%
“…Jackson et al (1988) reported an elastic modulus of approximately 70 GPa (dry) and 60 GPa (wet) from the shell of a bivalve mollusc, Pintada umbricata, and a tensile strength of approximately 170 MPa (dry) and 130 MPa (wet). Sarikaya et al (1990) reported fracture toughness of approximately 8 MPa m 1/2 , measured using four-point bending tests, and a fracture strength of approximately 185 MPa in three-point bending tests, which are superior to that of many engineering ceramics. Fracture toughness is reported to increase in wet conditions.…”
Section: (G ) Seashellsmentioning
confidence: 95%
“…In fact, it seems clear that there are great differences in the site of deposition of the proteins, and therefore perhaps in their function in different biominerals. Thus, for example, nacre in abalone shells appears to be organized in layers of aragonite "bricks" sealed to each other by a "mortar" of proteins (1). In contrast, in the primitive skeleton (spicule) of the sea urchin, evidence has been reported in support of the proposal that the macromolecules are intercalated within the crystal lattice of calcite (2,3) and that this results in its novel mechanical properties.…”
mentioning
confidence: 99%